From small molecules to polymeric probes: recent advancements of formaldehyde sensors. Issue 1 (31st December 2022) - Pan, Swagata; Roy, Subhadip; Choudhury, Neha; Behera, Priyanka Priyadarshini; Sivaprakasam, Kannan; Ramakrishnan, Latha; De, Priyadarsi
ABSTRACT: Formaldehyde is a well-known industrial material regularly used in fishery, vegetable markets, and fruit shops for maintaining their freshness. But due to its carcinogenic nature and other toxic effects, it is very important to detect it in very low concentrations. In recent years, amine-containing fluorescent probes have gained significant attention for designing formaldehyde sensors. However, the major drawbacks of these small molecular probes are low sensitivity and long exposure time, which limits their real-life applications. In this regard, polymeric probes have gained significant attention to overcome the aforementioned problems. Several polymeric probes have been utilized as a coating material, nanoparticle, quartz crystal microbalance (QCM), etc., for the selective and sensitive detection of formaldehyde. The main objective of this review article is to comprehensively describe the recent advancements in formaldehyde sensors based on small molecules and polymers, and their successful applications in various fields, especially in situ formaldehyde sensing in biological systems. Abstract : uf0001